(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
Toxocariasis is a neglected zoonosis with a high prevalence and impact on the public health of impoverished populations in the world, its causative agent is the nematode of the genus Toxacara. Broad-spectrum antiparasitics are currently used to deal with the disease, however, there is no vaccine to prevent it. The objective of this research was to evaluate the biological safety of experimental clinical trials of reverse vaccinology; and also, to evaluate the in vitro response of PBMC of canines previously vaccinated with the recombinant proteins rTcVcan and rTcCad of Toxocara canis, through the gene expression assay measured by RT-qPCR of IL-5, IL-6, IL-17. , IL-10, TNF-α and INF-Ɣ cytokines. As result, once the clinical trials for the vaccination of the puppies were carried out, no differences were observed with respect to the reference ranges of the hematology analysis, as well as the analyzes of the liver and kidney functions in the puppies and; on the other hand, in the gene expression assays in PBMC, only the ACTB gene was successfully expressed, the cytokine genes did not present statistically significant results. In conclusion, the applied formulations were not toxic and had no adverse effects on the experimental animals and gene expression assays in PBMC of vaccinated puppies with the recombinant rTcVcan and rTcCad proteins against T. canis did not show conclusive results regarding the success of these procedures in the first phase of the experimental vaccine.